Immobilization of Pseudomonas sp. DG17 onto sodium alginate–attapulgite–calcium carbonate - Wang, Hong Qi (Biotechnol Biotechnol Equip, 2014)
A strain of Pseudomonas sp. DG17, capable of degrading crude oil, was immobilized in sodium alginate–attapulgite–calcium carbonate for biodegradation of crude oil contaminated soil. In this work, proportion of independent variables, the laboratory immobilization parameters, the micromorphology and internal structure of the immobilized granule, as well as the crude oil biodegradation by sodium alginate–attapulgite–calcium carbonate immobilized cells and sodium alginate–attapulgite immobilized cells were studied to build the optimal immobilization carrier and granule-forming method. The results showed that the optimal concentrations of sodium alginate–attapulgite–calcium carbonate and calcium chloride were 2.5%–3.5%, 0.5%–1%, 3%–7% and 2%–4%, respectively. Meanwhile, the optimal bath temperature, embedding cell amount, reaction time and multiplication time were 50–60 °C, 2%, 18 h and 48 h, respectively. Moreover, biodegradation was enhanced by immobilized cells with a total petroleum hydrocarbon removal ranging from 33.56% ± 3.84% to 56.82% ± 3.26% after 20 days. The SEM results indicated that adding calcium carbonate was helpful to form internal honeycomb-like pores in the immobilized granules.